A Model‐Based Analysis of Physical and Biogeochemical Controls on Carbon Exchange in the Upper Water Column, Sea Ice, and Atmosphere in a Seasonally Ice‐Covered Arctic Strait. Issue 10 (29th October 2018) - Mortenson, Eric; Steiner, N.; Monahan, A. H.; Miller, L. A.; Geilfus, N.‐X.; Brown, K.
Abstract: In this study, we consider a 1‐D model incorporating both sea ice and pelagic systems in order to assess the importance of various processes on the vertical transport and exchange of carbon in the seasonally ice‐covered marine Arctic. The model includes a coupled ice‐ocean ecosystem, a parameterization of ikaite precipitation and dissolution, a formulation for ice‐air carbon exchange, and a formulation for brine rejection and freshwater dilution of dissolved inorganic carbon (DIC) and total alkalinity (TA) associated with ice growth and melt. Sensitivity analyses illustrate that (1) the pelagic ecosystem accounts for more than half of the net ocean carbon uptake, but ice algae have little effect on the air‐sea exchange in the standard run; (2) inclusion of ikaite precipitation and dissolution do not strongly affect the net ocean carbon uptake for concentrations within the observed range but can become important for larger concentrations; (3) varying DIC and TA in the ice by equal amounts, or varying brine deposition depth, does not affect the net ocean carbon uptake, because the coincident changes in TA and DIC concentrations at the sea surface serve to counteract one another with respect to sea surface p CO2 ; and (4) the proportions of carbon released to the water column (versus to the atmosphere) during ice growth and melt are important quantities to constrain in order to determine the contribution of the combined ice‐ocean system to oceanic uptake of atmospheric carbon. Plain Language Summary: Carbon dioxide is being taken up by the global oceans, especially at the poles. Although sea ice has been treated as a barrier to air‐sea exchange of gases, recent observations have shown that it is not so simple. This study uses a model to represent loss, gain, and movement of inorganic carbon due to sea ice growth and melt, ice and water column ecosystems, and air‐sea exchange in the open‐water season. Results from this study indicate that the ecosystem is a major player in the uptake of carbon dioxide by the Arctic Ocean and that fundamental processes relating to the sea ice need to be further studied, in particular, (a) how ice (low in inorganic carbon) is created from seawater (high in inorganic carbon) and (b) the formation of carbon‐containing crystals in sea ice. Key Points: We present a 1‐D model of the vertical transport of inorganic carbon including both biological and ice carbon pumps Ice‐associated developments include transport of inorganic carbon through brine, ice melt, and air‐ice CO2 exchange Marine pelagic productivity accounts for more than half of the simulated net ocean CO2 uptake, with a small contribution from ice algae